2019
DOI: 10.1111/1365-2664.13363
|View full text |Cite
|
Sign up to set email alerts
|

The significance of retention trees for survival of ectomycorrhizal fungi in clear‐cut Scots pine forests

Abstract: 1. Forestry with short stand generations and simplified forest structures has markedly affected forest biodiversity. One group of organisms adversely affected by clear-cutting is ectomycorrhizal (ECM) fungi, as they are associated with the roots of living trees. Retention forestry is a way of reducing logging impacts and enhancing biodiversity conservation. Increasing the proportion of trees retained at harvest may improve ECM fungal diversity.2. We investigated the potential for lifeboating of ECM fungi throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 43 publications
1
23
0
1
Order By: Relevance
“…In selectively harvested plots, the decline in overall fungal richness was related to decrease in EcM fungi and yeasts. Our results are thus partly consistent with a study in Northern Sweden that found 30-40% decline in EcM fungal diversity in a few years after partial harvesting (Sterkenburg et al, 2019) but in a disagreement with studies in Spanish Mediterranean forests revealing no effect (Castano et al, 2018a;Parlade et al, 2019). However, our study corroborates the long-term selective harvesting effect on composition of fungi and specifically EcM fungi in Mediterranean forests, which was not evident in Sweden.…”
Section: Forest Managementsupporting
confidence: 81%
See 2 more Smart Citations
“…In selectively harvested plots, the decline in overall fungal richness was related to decrease in EcM fungi and yeasts. Our results are thus partly consistent with a study in Northern Sweden that found 30-40% decline in EcM fungal diversity in a few years after partial harvesting (Sterkenburg et al, 2019) but in a disagreement with studies in Spanish Mediterranean forests revealing no effect (Castano et al, 2018a;Parlade et al, 2019). However, our study corroborates the long-term selective harvesting effect on composition of fungi and specifically EcM fungi in Mediterranean forests, which was not evident in Sweden.…”
Section: Forest Managementsupporting
confidence: 81%
“…It has been argued that the diversity of soil organisms is of particular importance for ecosystem services and resilience to disturbances, with a potential to ameliorate stress caused by global change ( Langenheder et al, 2010 ; Bardgett and van der Putten, 2014 ). Many of these soil organisms are vulnerable to shifts in land use, changing climate and ecosystem management ( Van der Putten, 2013 ; George et al, 2019 ; Makiola et al, 2019 ; Sterkenburg et al, 2019 ); therefore, some of the most conspicuous rare species are protected ( Dahlberg et al, 2010 ). However, fungal species that have large fruitbodies represent only a tip of the iceberg in the enormous diversity of soil mycobiome, much of which is cryptic and previously undocumented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results cannot by themselves be used to determine whether this is sufficient to maintain biodiversity in accordance with the objectives in the Forestry Act, although it demonstrates that today's clearcuts are more structurally diverse than those 50 years ago. This structural diversity has at least the potential to support comparatively more biodiversity and other studies, with focus on how retention forestry affect species taxa and functional groups, show positive effects on abundance and richness both in short and long term perspective (Franklin, Macdonald, & Nielsen, 2019;Pastur et al, 2019;Savrak, Remm, & Lohmus, 2019;Sterkenburg, Clemmensen, Lindahl, & Dahlberg, 2019). However, assessing the extent to which current practices actually supports critical species is outside the scope of this work.…”
Section: Discussionmentioning
confidence: 93%
“…The aims were to nd out how nematode community structure (species composition and diversity) were in uenced; i) by host age (in ewes and lambs), ii) in the shortterm following recent anthelmintic treatment with ABZ, IVM or LEV, and iii) long-term in samples collected several years apart. For this we used DNA extracted from composite larval cultures which then were analyzed using a PacBio NGS pipeline generating sequence data (amplicons) that were clustered into OTUs with a speci cally designed analysis framework developed for eukaryotes (SCATA) [33][34][35]. We identi ed ve common OTUs representing 97% of the reads, among which H. contortus and T. circumcincta were the two dominant species.…”
Section: Discussionmentioning
confidence: 99%